Negative Risk Markers for Cardiovascular Risk Evaluation in Chinese Adults - Bie, Lizhan; Niu, Jingya; Wu, Shujing; Zheng, Ruizhi; Xu, Min; Lu, Jieli; Wang, Tiange; Zhao, Zhiyun; Wang, Shuangyuan; Lin, Hong; Dai, Meng; Zhang, Di; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background The atherosclerotic cardiovascular disease (ASCVD) risk predicted by traditional risk factors is used to guide preventive treatment. We aimed to investigate whether preferable levels of non-traditional emerging risk factors (i.e., negative risk markers) could downgrade the predicted ASCVD risk beyond traditional risk factors. Methods A total of 7,568 Chinese adults aged ≥ 40 years were followed up during 2010–2015. Negative risk markers including non-traditional lipids, urinary albumin-to-creatinine ratio, electrocardiogram (ECG), and measurements of atherosclerosis were evaluated using diagnostic likelihood ratio (DLR) and continuous net reclassification index (NRI) for their ability to downshift predicted CVD risk in the overall study population and in participants with intermediate (traditional risk factor predicted ASCVD risk 7.5% to 19.9%) or high risk (≥20%). Results During a median follow-up of 4.5 years, 416 participants developed CVD events including non-fatal myocardial infarction, non-fatal stroke, and cardiovascular death. Among negative risk markers examined, lipoprotein(a) ≤ 10th percentile (5 mg/dL), normal ECG, and carotid intima-media thickness (CIMT) ≤ 25th percentile (0.5 mm) provided moderate CVD risk reclassification and downward changes in pre- to post-test risk on top of the traditional CVD risk factors, especially in high-risk participants. The DLRs were 0.41, 0.75, and 0.41, and the NRIs were 18, 22, and 14% for lipoprotein(a), ECG, and CIMT, respectively in high-risk participants. Conclusions Lipoprotein(a) ≤ 5 mg/dL, normal ECG, and CIMT ≤ 0.5 mm might be used as negative non-traditional risk markers to correctly downgrade predicted ASCVD risk in Chinese adults.